Socialization of MSME Marketing Innovation in Facing Trade Tariff Increases - Muhammad Tohir; Aang Gunawan; Abdullah Ade Suryo; Cecep Pahrudin; Sugiyanto Sugiyanto (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The increase in trade tariffs is a serious challenge for Micro, Small, and Medium Enterprises (MSMEs) in maintaining the competitiveness of their products in domestic and international markets. This community service activity aims to provide understanding and practical skills to MSMEs about adaptive and sustainable marketing strategy innovations. Socialization is carried out through workshops and interactive discussions involving MSMEs from various sectors. The material presented includes the use of digital media, increasing product branding, market diversification, and competitive pricing strategies. The activity results show an increase in participants' knowledge in implementing innovative marketing approaches and awareness of the importance of digital transformation in dealing with external pressures such as increasing trade tariffs. Thus, this activity is expected to strengthen MSME resilience and encourage sustainable business growth. This activity also opens up opportunities for further collaboration between academics and MSMEs in developing strategic solutions based on real needs in the field.